The influence of parents and the home environment on preschoolers' physical activity behaviours: A qualitative investigation of childcare providers' perspectives - Irwin Jennifer D; Burke Shauna M; van Zandvoort Melissa M; Tucker Patricia (BMC, 2011)
Abstract Background Physical activity offers numerous physiological and psychological benefits for young children; however, many preschool-aged children are not engaging in sufficient activity. The home environment, inclusive of parent role modeling, has been identified as influencing preschoolers' physical activity. This study sought to examine childcare providers' perspectives of the importance of parents and the home environment for supporting the physical activity behaviours of preschool-aged children (aged 2.5-5 years) attending childcare. Methods A heterogeneous sample of childcare providers (n = 84; response rate 39%) working at childcare facilities in London, Ontario participated. Thirteen semi-structured focus groups were conducted in London centres between February 2009 and February 2010. Focus groups were audio recorded and transcribed verbatim and inductive content analysis was used to code and classify themes. A number of strategies were used to verify the trustworthiness of the data. Results Childcare providers acknowledged their reliance on parents/guardians to create a home environment that complements the positive physical activity messaging children may receive in childcare. Moreover, childcare staff highlighted the need for positive parent role modeling and parent support to encourage active healthy lifestyles among young children. Conclusion This study's findings highlight the need for increased parent-caregiver partnering in terms of communication and cooperation in service of promoting appropriate amounts of physical activity among London preschoolers.